Integrating Computational Analysis of In Vivo Investigation of Modulatory Effect of Fagonia cretica Plant Extract on Letrozole-Induced Polycystic Ovary Syndrome in Female Rats - Ayesha Qasim; Hiram Calvo; Jesús Jaime Moreno Escobar; Zia-ud-din Akhtar (Biology)
Fagonia cretica, a medicinal herb from the Zygophyllaceae family, is traditionally utilized to treat various conditions such as hepatitis, gynecological disorders, tumors, urinary tract issues, and diabetes. The present study aimed to evaluate the therapeutic potential of Fagonia cretica in treating polycystic ovarian syndrome (PCOS) induced in female rats. PCOS, a complex hormonal disorder, was experimentally induced by administering Letrozole (1 mg/kg) in combination with a high-fat diet for 21 days. The affected rats were then treated with hydro-alcoholic extracts of Fagonia cretica at doses of 100 mg/kg, 200 mg/kg, and 300 mg/kg for 20 days. Key biochemical parameters—including serum testosterone, insulin, fasting blood glucose, insulin resistance (HOMA-IR), cholesterol, triglycerides, and lipoprotein levels—were measured. Ultrasound imaging and histopathological analysis of ovarian tissues were also performed. The data were analyzed using computer-based statistical tools, including one-way ANOVA, Cohen’s d effect size, and Tukey’s HSD test, with graphical representations generated using Python 3.10 on the Kaggle platform. Results demonstrated a significant reduction in serum testosterone, insulin, cholesterol, and triglyceride levels (p < 0.05) in treated groups, along with improved ovarian morphology. These findings support the therapeutic potential of Fagonia cretica as a natural treatment for PCOS.